A modern approach to monetary and fiscal policy. (March 2022) - Junior, Celso J. Costa; Garcia-Cintado, Alejandro C.; Junior, Karlo Marques
Abstract: This paper puts forth a systematic approach to teaching fiscal-monetary interactions that follows the view of one of the fathers of the Fiscal Theory of the Price Level (FTPL), Eric Leeper. The main advantage of this setup is its simplicity, which makes it particularly suited for undergraduates and non-specialists. It relies on a two-graph device to show that fiscal and monetary policies always get determined simultaneously and that their effects on the economy always depend on one another's behavior. It is straightforward to see that in a conventional monetarist world (Regime M), the central bank succeeds in controling inflation so long as the fiscal authority does its job of ensuring that public debt does not grow too much. By contrast, in an alternative fiscal-dominant regime (Regime F), fiscal policy determines the price level (and inflation) in the short run, and the optimal monetary stance is holding the policy rate constant, since if the central bank otherwise tries to fight back fiscally determined inflation, it will worsen fiscal sustainability and increase future inflation.